PEMIKIRAN EKONOMI KLASIK - Arsad Halomoan Sipahutar (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2022)
Humankind’s existence in this world is inseparable from economic activity, it is related to how humans do activities in fulfiling their life needs. Even said humans are economic beings. This developments of the economy in the present, especiallyin welfare studies has a variety of features, there are so called feudal, capitalist, and so forth. Thougts arise from pattern. The failure of the conventional economic system triggered the resurgence of the Islamic economic system. With proven start in every area of the spirit in developing and reviewing the economy of Islam or sharia economy. Though the study of Islamic economics is not a new thing. He was born together with the coming of Islam. Therefore we need to know how the classical economic thingking, especially in the view of Muslim economic thingkers